TINDAK TUTUR DIREKTIF GURU DAN SISWA PADA PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH MENENGAH PERTAMA (SMP) - Septia Uswatun Hasanah (LPPM STKIP PGRI Bandar Lampung, 2019)
The problem discussed in this study is how the teacher's speech acts in learning specifically the directive speech acts in Indonesian language learning in junior high schools. The purpose of this study is to describe the forms of directive speech acts in Indonesian language learning in junior high schools. This study used descriptive qualitative method. The data source in this study is the speech acts used by teachers and students in learning Indonesian. Data collection techniques in this study using observation techniques, and data analysis techniques used in this study are heuristic analysis techniques. The results showed that the directive speech act function was found when learning in class. The directive speech acts that dominate teacher and student speech are direct directives.